2022
DOI: 10.3390/polym14132689
|View full text |Cite
|
Sign up to set email alerts
|

Study on Bond-Slip Behavior between Seawater Sea-Sand Concrete and Carbon Fiber-Reinforced Polymer (CFRP) Bars with Different Surface Shapes

Abstract: The application of CFRP bar and seawater sea-sand concrete (SSSC) in construction can overcome the shortcomings in conventional reinforced concrete, such as corrosion induced by carbonation and chloride ingress. In this study, the bond-slip behavior between an SSSC cube and CFRP bar has been investigated, and different CFRP bar surface shapes have been considered. A total of 27 specimens (9 groups) were fabricated for a pull-out test, where three types of CFRP bar with different surface shapes were used: smoot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…With the development of FRP materials, FRP bars became more common in the construction industry, which made it crucial to predict the bond-slip process between FRP bars and concrete. Several bond-slip constitutive models of FRP bars with high recognition were developed as a result of continuous research by scholars [ 45 ]. Comparing the fitted bond-slip curve results from various models allowed us to assess the applicability of each bond-slip constitutive model in this experimental study.…”
Section: Resultsmentioning
confidence: 99%
“…With the development of FRP materials, FRP bars became more common in the construction industry, which made it crucial to predict the bond-slip process between FRP bars and concrete. Several bond-slip constitutive models of FRP bars with high recognition were developed as a result of continuous research by scholars [ 45 ]. Comparing the fitted bond-slip curve results from various models allowed us to assess the applicability of each bond-slip constitutive model in this experimental study.…”
Section: Resultsmentioning
confidence: 99%
“…The bond behavior between concrete and FRP bars was investigated to prevent mode failure. For example, Gao et al [ 61 ] analyzed the bond–slip behavior between seawater sea sand concrete and CFRP bars with different surface shapes using a pull-off test. The results indicated that the ribbed bar has a significantly higher bond strength than the regular bar.…”
Section: Research Progressmentioning
confidence: 99%
“…It has been limited primarily to the investigation of anchoring length; that is, the bond effect [21,22]. This, among other things, is also concerned with numerical testing [23][24][25][26]. Recommendations for required anchoring lengths in cases of the classical way of cut-off splicing via longitudinal overlapping (as for steel reinforcement) relate to manufacturer's data for specific materials, shapes, and surface treatments of the additional FRP reinforcement [20], and relate to limited classic lap splice research recommendations [27][28][29].…”
Section: Introductionmentioning
confidence: 99%